EFFECTIVENESS OF IMMUNOSUPPRESSANTS ALONG WITH ACEI/ARBS IN TREATING PROTEINURIA IN PATIENTS WITH SOLITARY KIDNEY POST NEPHRECTOMY - Azam, Nadeem; Siddiqi, Fuad Ahmad; Javed, Koukab; Butt, Batool (Pakistan Armed Forces Medical Journal, 2018)
Objective: To ascertain the effectiveness of immunosuppressants along with ACEI and /or ARBS in proteinuria in patients with solitary kidney post nephrectomy. Study Design: Prospective quasi-experimental study. Place and Duration of Study: Combined Military Hospital Peshawar and Multan, from 2010 to 2016. Subjects and Methods: The sample population comprised of 07 cases of post nephrectomy solitary kidney developing proteinuria from 2010-2016 reporting to hospitals. Patients were given initially ACEI and/or ARBS to lower proteinuria for three months. They were followed up to see for complete or partial remission. Deltacortil 1mg/kg max 60mg/day along with ACEI and /or ARBS was added to patients who didn’t go into remission. Results: Out of 7 patients, 3 (42.9%) were males and 4 (57.1%) were female patients. Addition of deltacortil 1mg/kg max 60mg/day along with ACEI and /or ARBS reduced proteinuria to less than 1 gram in 3 patients (2 males and 1 female) and less than 300mg in 4 patients (1 male and 3 females).There was a reduction in the mean 24hrs urinary protein excretion as a whole from the baseline 2.33 ± 0.84 g/24 hrs to 0.48 ± 0.33 g/24 hrs. Remission was achieved on the average in three months and maintenance on tapering doses for 12 months. Cyclosporine was used in three cases who relapsed on tapering steroids and remission was achieved with 5-10mg steroids and 100-200mg of cyclosporine. Conclusion: Non respondent patients with solitary kidney developing proteinuria being treated with ACEI and /or ARBS had good chance to lower their proteinuria with steroids. Relapses even with steroids responded to cyclosporine.